Energy harvester using PZT nanotubes fabricated by template-assisted method - Jung, Woo-Suk; Do, Young-Ho; Kang, Min-Gyu; Kang, Chong-Yun (ELSEVIER, 2013)
Lead zirconate titanate (PZT) nanotubes fabricated by template-assisted method using sol-gel solution infiltration are applied for energy harvester. To fabricate PZT nanotubes, an anodic aluminum oxide is used for the template, and as-prepared PZT solution dropped on the surface of the AAO is infiltrated by vacuum pump into the pores in the AAO. The template including PZT solution is dried at 80 degrees C for 1 min and dried again at 300 degrees C for 10 min, and then it treated at 650 degrees C for 30 min to anneal PZT and form the expected perovskite phase. The fabricated nanotubes were mixed with PDMS polymer composite and polyimide films coated Pt/Ti were used for electrodes. Finally, it demonstrated that the energy harvester could generate the output power of 37 nW/cm(2). (C) 2013 Elsevier B.V. All rights reserved.
Keywords: NANOGENERATOR; GROWTH